Detecção e caracterização molecular de Sarcocystis spp. em tecidos de ovinos abatidas em frigoríficos no Sul do Brasil - Minuzzi, Camila Encarnação (2018)
Sarcocystis spp. are intracellular protozoan parasites with an intermediate-definitive host life cycle and can infect a wide range of animals. There are some differences among the Sarcocystis species related to the life cycle and pathogenicity, but the formation of tissue cysts is a common characteristic within the genus. In sheep, Sarcocystis species that commonly cause infection are Sarcocystis tenella, Sarcocystis arieticanis, Sarcocystis gigantea and Sarcocystis medusiformis. S tenella and S. arieticanis present canids as definitive hosts, form microscopic cysts and can cause clinical disease or subclinical infection. On the other hand, S. gigantea and S. medusiformis which have felids as definitive hosts form macroscopic cysts and, although these Sarocystis species do not have pathogenic potential in sheep, the presence of macrocysts cause condemnation of sheep meat and organs. Sarcocystosis is a widespread infection, with high occurrence rates mainly in developing countries. Although some studies have already demonstrated the presence of Sarcocystis species in sheep breeding in Brazil, more knowledge about sheep Sarcocystosis epidemiology is essential. Therefore, the aims of this study were to investigate the occurrence of Sarcocystis spp. in sheep slaughtered in Santa Maria and Santiago, as well as to check the presence of Sarcocystis spp. DNA in the evaluated samples and to identificate the Sarcocystis species through genetic sequencing. A part of the18S rDNA gene was selected for PCR amplification, followed by genetic sequencing aiming Sarcocystis species identification. Ten of the 130 sheep had macrocysts and all of these macrocysts were confirmed as S. gigantea. Micro cysts were found in 125 animals. All microcysts were of the Sarcocystis genus as shown by PCR amplification. Ten of these samples, randomly selected for gene sequencing, were confirmed as S. tenella. The frequency of microscopic cysts was high, although this is not surprising. Macroscopic cysts were found only in the esophagus. This study presents the first molecular confirmation of the presence of S. gigantea in Brazil.